The Influence of Perceived Quality, Brand Awareness, and Price Suitability on Customer Satisfaction and Its Impact on Repurchase Intention of NPK Plus Fertilizer at CV Putra Daerah Jaya - Balqis, Ken Fajri Amelia; Sumekar, Kertati; Sunarno, Agustinus (International Journal of Science and Society, 2025)
The marketing system of every company aims to achieve its organizational objectives. This study analyzes the influence of perceived quality, brand awareness, and price on repurchase intention, with customer satisfaction as a mediating variable, among farmers of CV Putra Daerah Jaya. The research involved a sample of 140 respondents selected through purposive sampling. Data were analyzed using the Structural Equation Model (SEM) approach with AMOS software. The findings reveal that perceived quality has a positive but statistically insignificant effect on repurchase intention, indicating that an increase in product quality perception does not significantly enhance repurchase intention. In contrast, brand awareness exerts a positive and significant influence on repurchase intention, suggesting that strengthening brand awareness encourages repeat purchases among farmers. Meanwhile, price suitability shows no significant impact on the repurchase intention of NPK Plus fertilizer. Perceived quality, brand awareness, and price suitability all have positive and significant effects on farmer satisfaction. Furthermore, customer satisfaction has a positive and significant effect on farmers repurchase intention, implying that improving satisfaction can lead to higher repurchase intention. The study also finds that customer satisfaction can mediate the relationship between perceived quality and brand awareness to repurchase intention but not significant, and customer satisfaction can mediate price suitability price on farmers repurchase intention.